2018
DOI: 10.1021/acs.inorgchem.8b02177
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Auranofin and Its Pseudohalide Derivatives with Serum Albumin Investigated through ESI-Q-TOF MS

Abstract: The reactions of auranofin and three pseudohalide derivatives with bovine serum albumin were explored by ESI-Q-TOF mass spectrometry; a detailed molecular description of the resulting adducts is achieved revealing even subtle differences in reactivity within this series of gold(I) complexes. Our study shows that this kind of investigative approach, formerly applied to the interactions of metal-based drugs with small model proteins of MW 10-15 kDa, e.g., cytochrome c and lysozyme, may now be extended with succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 34 publications
4
60
0
Order By: Relevance
“…Thus, we performed ESI-MS experiments also for AF and AF-I incubated with the two latter amino acids. Results confirmed the lack of reactivity for these two target molecules with AF and AF-I, further supporting the findings already published by some of us regarding the reactivity of auranofin and its derivatives toward protein targets (Landini et al, 2017;Pratesi et al, 2018;Zoppi et al, 2020).…”
Section: Esi Mass Spectrometrysupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, we performed ESI-MS experiments also for AF and AF-I incubated with the two latter amino acids. Results confirmed the lack of reactivity for these two target molecules with AF and AF-I, further supporting the findings already published by some of us regarding the reactivity of auranofin and its derivatives toward protein targets (Landini et al, 2017;Pratesi et al, 2018;Zoppi et al, 2020).…”
Section: Esi Mass Spectrometrysupporting
confidence: 90%
“…Starting from our previous findings on the reactivity of AF and its analogs toward protein targets (Pratesi et al, 2014(Pratesi et al, , 2018Marzo et al, 2017Marzo et al, , 2019Cirri et al, 2019;Zoppi et al, 2020), here we have extended the investigation-at the molecular levelon the mode of action of these medicinally relevant gold(I) compounds. Specifically, we have focused our attention on AF and its analog where the thiosugar moiety is replaced by the iodide ligand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These time course results demonstrate that AF is far more labile exchange inert than originally thought. [108]. Note that metal-free BSA consists of several post translational modifications (PTMs) and only the Cys34 with no PTM is able to coordinate directly to Au(I).…”
Section: Modifying the Phosphine And Thiosugar Ligands Of Auranofin Tmentioning
confidence: 99%
“…This prompted investigators to analyze in detail the reactions of medicinal gold compounds with proteins. A systematic investigation on the interactions of the reference gold(I) drug auranofin with a series of model proteins, i.e., human serum albumin, carbonic anhydrase, superoxide dismutase, and hemoglobin, was recently carried out in our laboratory through mass spectrometry, and the resulting adducts could be characterized in molecular detail (Pratesi et al, 2016(Pratesi et al, , 2018(Pratesi et al, , 2019Magherini et al, 2018;Cirri et al, 2019;Zoppi et al, 2020). These studies revealed that auranofin targets quite selectively the free cysteine residues of proteins (Pratesi et al, 2018;Zoppi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%